2022
DOI: 10.1186/s40249-022-00998-6
|View full text |Cite
|
Sign up to set email alerts
|

Mass drug administration of antibacterials: weighing the evidence regarding benefits and risks

Abstract: Background Mass drug administration (MDA) is a strategy to improve health at the population level through widespread delivery of medicine in a community. We surveyed the literature to summarize the benefits and potential risks associated with MDA of antibacterials, focusing predominantly on azithromycin as it has the greatest evidence base. Main body High-quality evidence from randomized controlled trials (RCTs) indicate that MDA-azithromycin is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
4
1
Order By: Relevance
“…41 In this report, there was an 8.9(AOR = 8.9:95%; 12 months of treatment as compared with control groups supporting the use of MDA-azithromycin in trachoma control as being highly acceptable. 42,43 Unlike previous studies, finding in central Ethiopia, 44 Southern Ethiopia, 45 and Tanzania 46 demonstrated that our study had no evidence of distance to drinking water sources, distance to health facilities, and many families and no significant association with acquiring to develop active trachoma infection. Individuals who lived near water sources had higher hygiene standards, more personal cleanses, and a lower risk of trachoma infection from flies, which is directly related to the likelihood of developing Trachoma.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…41 In this report, there was an 8.9(AOR = 8.9:95%; 12 months of treatment as compared with control groups supporting the use of MDA-azithromycin in trachoma control as being highly acceptable. 42,43 Unlike previous studies, finding in central Ethiopia, 44 Southern Ethiopia, 45 and Tanzania 46 demonstrated that our study had no evidence of distance to drinking water sources, distance to health facilities, and many families and no significant association with acquiring to develop active trachoma infection. Individuals who lived near water sources had higher hygiene standards, more personal cleanses, and a lower risk of trachoma infection from flies, which is directly related to the likelihood of developing Trachoma.…”
Section: Discussioncontrasting
confidence: 84%
“…In this report, there was an 8.9(AOR = 8.9:95%; 2.36‐‐33.6, p = 0.01) time increase for active trachoma infection if mass drug administration of Azitromza as part of chemoprophylaxis for prevention. A recent Cochrane review of four cluster randomized trials (RCTs) that compared community‐level treatment with MDA‐azithromycin showed a reduction of 40–60% active trachoma within 12 months of treatment as compared with control groups supporting the use of MDA‐azithromycin in trachoma control as being highly acceptable 42,43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass periodic distribution of azithromycin clearly selects for macrolide-resistant bacteria. 22 Increased resistance in Streptococcus pneumoniae and Escherichia coli has been well documented following mass azithromycin distribution for trachoma. 23 The prevalence of macrolide resistance appears to decline after mass distributions are discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…The ermB gene was found in 9% of pneumococci, and is associated with macrolide resistance (40). Future improved understanding of antimicrobial resistance in pneumococci would be useful to better understand the impact of more clinically-relevant antibiotics for standard care as well as the potential impact of mass-drug administration campaigns, a potential alternative intervention to reduce the pneumococcal disease burden proposed for crisis settings (41).…”
Section: Discussionmentioning
confidence: 99%